KONTRIBUSI KEMAMPUAN MANAJERIAL DAN GAYA KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KINERJA GURU - Sari, Ruly Nadian; Muhtarom, Muhtarom; Hamid, Abdul (STIT Pringsewu, 2016)
The reseach was intended to discover the contribution the managerial of capability and stlye of leadership on teacher of kinerja. The research uses a quantitative method with sampling probability sampling technique with a sample of 33 people in Junior High School districts North of Kotabumi districts North of Lampung. The results showed a contribution of between managerial ability and leadership style of principals on teacher performance. This means that the ability of managerial and leadership styles have a significant contribution to the performance of teachers either partially or tested together.